Modern Approaches to H. pylori Eradication Therapy in Adults (Literature Review and Resolution of Experts Council) - V. Т. Ivashkin; A. I. Ulyanin; I. V. Mayev; R. S. Kozlov; M. A. Livzan; S. R. Abdulkhakov; O. P. Alekseyeva; S. A. Alekseyenko; D. S. Bordin; N. N. Dekhnich; N. V. Korochyanskaya; T. L. Lapina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze current approaches to H. pylori eradication therapy in adults and present the materials of Experts Council held on December 9, 2022 in Moscow.General statements. H. pylori infection is the main etiological factor of gastritis, peptic ulcer, and gastric cancer. Eradication of H. pylori is recognized as a necessary measure to reduce the incidence of these diseases. The approaches to selecting an eradication regimen should be optimized to take into account epidemiological trends and achieve better treatment outcomes. The updated Maastricht VI Consensus Report presents the means to overcome the difficulties in selecting an approach to the treatment of H. pylori infection. However, eradication therapy remains challenging due to adverse events (primarily antibiotic-associated diarrhea), poor treatment tolerance and patient compliance. Eradication therapy can be optimized by supplementing treatment regimens with strain-specific probiotics that reduce adverse events, improve patient compliance and eradication rates, such as Saccharomyces boulardii CNCM I-745 strain with established efficacy.Conclusion. The inclusion of certain probiotics in eradication regimens improves treatment tolerance, reduces the risk of adverse events, improves patient compliance and eradication rates.